Editorial of the Special Issue Digital Soil Mapping, Decision Support Tools and Soil Monitoring Systems in the Mediterranean - Giuseppe Lo Papa; Calogero Schillaci; Maria Fantappiè; Giuliano Langella (Land, 2024)
In the digital era, the role of soil surveyors has evolved significantly [...]